Awareness, Attitude and Utilization of Orange-Fleshed Sweet Potato (OFSP): Critical Literature Review - Abujaja Afishata Mohammed (European Scientific Journal, ESJ, 2023)
The objectives of the study seek to review literature to establish the attitude, level of awareness and the extent of OFSP utilization. The study relied on secondary sources to synthesize and draw conclusions regarding the topic. The researcher reviewed a variety of documents and the data collected from previous published articles, journals, websites, original research papers and books to establish the awareness, attitude and utilization of OFSP. The review was supposed to offer important information regarding how widely used and known OFSP was. Evidence from the study showed that although most countries in the world were aware of OFSP's existence and nutritional advantages, the market for OFSP was not yet formally established. Most of the studies used emphasized that if OFSP is being processed into flour for making chips, biscuits, porridge, bread, drinks and other special forms of foods, consumers especially households would have accepted them to increase consumption. Socio-economic factors such as social class affect the level of utilization and preference patterns of the crop. Lack of storage facilities, lack of modern processing equipment and scarcity of OFSP vines had a great effect on its utilization. The study recommends that to increase agricultural value addition, OFSP farmers should be empowered through effective and efficient extension training on the usage of modern processing techniques.  Also, OFSP should be processed into several foods for alternative income sourcing. Finally, it is recommended that future studies be conducted on consumers’ willingness to pay for value-added products made from OFSP.